Columnar aerosol measurements in a continental southeastern Europe site: climatology and trends - Carstea, Emil; Fragkos, Konstantinos; Siomos, Nikolaos; Antonescu, Bogdan; Belegante, Livio (My University, 2019)
Monitoring of aerosols and their temporal evolution is very important for climate and air quality studies. In this study, we present a climatology of aerosol optical and microphysical properties over a continental southeastern European area based on 9 years of observations from a Cimel sun-photometer operating at Magurele (Romania) in the framework of AErosol RObotic NETwork (AERONET). The site is characterized by high intra-annual and inter-annual variability of the total aerosol optical depth (AOD), which has two peaks, during March and August. For half year, from May to November, Magurele is affected by the transport of aerosols from the nearby city of Bucharest, since the dominant winds are from this direction. Thus, the predominant is the fine mode of aerosols. The high inter-annual and intra-annual variability of Angstrom exponent (440–870 nm) indicates the presence of aerosols of different sizes. Negative statistically significant trends at all AOD wavelengths, the order of 20–40% per decade, have been calculated for the 9-year period of study (2007–2016). These trends are mostly attributed to the reduction of the fine mode particles, showing that the implementation of the EU regulations for the decrease of particulate matter emissions in Bucharest has been beneficial.
Keywords: Bucharest [Bucharest (ADS); Bucharest [Romania]; Romania; air quality; aerosol composition; annual variation; climatology; cloud microphysics; concentration (composition); optical depth; spatiotemporal analysis; trend analysis